Efektifitas Cognitive Behavioral Therapy (CBT) Dalam Mengatasi Kecemasan Social Pada Remaja - Hizbullah, Kahfi; Ariani, Dewinta (Jurnal Psikologi Jambi, 2025)
This study aims to examine the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing social anxiety in adolescents. Social anxiety disorders often emerge during adolescence and can hinder the development of social, academic, and emotional skills. CBT, as an evidence-based approach, has been widely used to treat anxiety disorders through cognitive restructuring, relaxation, and gradual exposure techniques. The method used is a single-case experimental design with an A-B design. The research subject is a 16-year-old adolescent who scored high on the Social Anxiety Scale for Adolescents (SAS-A) and met the diagnostic criteria for social anxiety disorder. The intervention was conducted over six sessions, focusing on identifying cognitive distortions, restructuring negative thoughts, relaxation exercises, and gradual exposure to social situations that trigger anxiety. The pre-test results showed a score of 85 (high category), while the post-test results showed a decrease to 61 (moderate category). The subject also demonstrated changes in the ability to think more realistically, courageously face social situations, and reduce avoidance behaviors. These findings indicate that the combination of techniques in CBT effectively helps the subject recognize cognitive distortions and develop more adaptive responses to social situations.